1992
DOI: 10.1086/269308
|View full text |Cite
|
Sign up to set email alerts
|

Biased Press or Biased Public? Attitudes Toward Media Coverage of Social Groups

Abstract: Mass media credibility has been defined and studied largely as an attribute of message sources. This article argues that trust in media can be better understood as a relational variable-an audience response to media content. In addition, audience assessments of credibility are commonly explained as the result of each individual's skeptical disposition, either toward mass media in particular or as a general trait. The author dissents from this view as well, proposing that distrust is more likely to be a situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
215
1
17

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(240 citation statements)
references
References 29 publications
7
215
1
17
Order By: Relevance
“…Dieser Zusammenhang wird in der Kommunikationswissenschaft mit dem so genannten Hostile-Media-Effekt (vgl. Vallone et al, 1985;Gunther, 1992) beschrieben und erklärt. In einer Vielzahl an Studien wurde der HostileMedia-Effekt bereits nachgewiesen (für eine Übersicht: Doty, 2005).…”
Section: Introductionunclassified
“…Dieser Zusammenhang wird in der Kommunikationswissenschaft mit dem so genannten Hostile-Media-Effekt (vgl. Vallone et al, 1985;Gunther, 1992) beschrieben und erklärt. In einer Vielzahl an Studien wurde der HostileMedia-Effekt bereits nachgewiesen (für eine Übersicht: Doty, 2005).…”
Section: Introductionunclassified
“…El punto de partida es que los receptores no son sujetos pasivos, aislados e imparciales, sino destinatarios "sociales" que evalúan al emisor e interpretan los mensajes según sus propios valores, actitudes y experiencias (Gunther 1992;Metzger et al 2003). A diferencia de la interpretación anterior, la credibilidad es entendida como el resultado de un juicio subjetivo y contextual de quienes reciben el mensaje (Tsfati 2003).…”
Section: La Confianza De La Opinión Pública En Los Medios De Comunclassified
“…The current literature provides abundant evidence for a so-called "Hostile Media Phenomenon" (Hansen & Kim, 2011;Vallone et al, 1985). Multiple studies have shown that people subjectively assess the degree of bias in news relative to their own political preferences: Liberals perceive a conservative bias in objective news, whereas conservatives perceive a liberal bias in the same news coverage (Gunther, 1992;Morris, 2007). This happens because people consider their own opinion as the outcome of objective analysis and, at the same time, find it is easy to believe that other opinions must be biased or simply wrong (Feldman, 2011b;Giner-Sorolla & Chaiken, 1994) in order to protect their self-esteem and reduce cognitive dissonance (Richardson, Huddy, & Morgan, 2008).…”
Section: Opinionated News and The Consequences Of The Hostile Media Pmentioning
confidence: 99%